Notes to Philosophy 167: Class 10 -- Huygens and the Beginnings of Rational Mechanics -- Part 8. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: The Initial Theory: Relative Motion Results -- Toward the Extended Theory: Proposition VIII -- The Extended Theory and its Consequences -- Empirical Evidence for the Two Theories -- Huygens on Circular Motion and Centrifugal Force: The Basic Conceptualization of the Problem.; Generally corresponds to the video segment: Class 10, Part 8.